Manganese concentrations in drinking water from villages near banana plantations with aerial mancozeb spraying in Costa Rica: Results from the Infants' Environmental Health Study (ISA) - van Wendel de Joode, Berna (2016)
Elevated manganese (Mn) in drinking water has been reported worldwide. While, naturally occurring Mn in groundwater is generally the major source, anthropogenic contamination by Mn-containing fungicides such as mancozeb may also occur. The main objective of this study was to examine factors associated with Mn and ethylenethiourea (ETU), a degradation product of mancozeb, in drinking water samples from villages situated near banana plantations with aerial spraying of mancozeb. Drinking water samples (n ¼ 126) were obtained from 124 homes of women participating in the Infants' Environmental Health Study (ISA, for its acronym in Spanish), living nearby large-scale banana plantations. Concentrations of Mn, iron (Fe), arsenic (As), lead (Pb), cadmium (Cd) and ethylenethiourea (ETU), a degradation product of mancozeb, were measured in water samples. Only six percent of samples had detectable ETU concentrations (limit of detection (LOD) ¼ 0.15 mg/L), whereas 94% of the samples had detectable Mn (LOD ¼ 0.05 mg/L). Mn concentrations were higher than 100 and 500 mg/L in 22% and 7% of the samples, respectively. Mn was highest in samples from private and banana farm wells. Distance from a banana plantationwas inversely associated with Mn concentrations, with a 61.5% decrease (95% CI: 97.0, 26.0) in Mn concentrations for each km increase in distance. Mn concentrations in water transported with trucks from one village to another were almost 1000 times higher than Mn in water obtained from taps in houses supplied by the same well but not transported, indicating environmental Mn contamination. Elevated Mn in drinking water may be partly explained by aerial spraying of mancozeb; however, naturally occurring Mn in groundwater, and intensive agriculture may also contribute. Drinking water risk assessment for mancozeb should consider Mn as a health hazard. The findings of this study evidence the need for health-based World Health Organization (WHO) guidelines on Mn in drinking water.